Analisis Manajemen Kesiswaan dalam Meningkatkan Kedisiplinan Siswa di MA Nurul Huda Sungai Luar" - Ahmad; Hasnawati, Hasnawati; Mardiah, Mardiah (Jurnal Edukasi, 2024)
This study aims to analyze the influence of student management on improving student discipline at MA Nurul Huda Sungai Luar. Effective student management is viewed as a key factor in creating a conducive learning environment and enhancing student discipline. This research employs a quantitative approach with a survey method. The research sample consists of 78 students selected using a saturated sampling technique. Data were collected through questionnaires, observations, and documentation. Data analysis utilized descriptive statistics and simple linear regression. The results indicate that student management has a positive and significant influence on student discipline (β = 0.685, p < 0.001), with 47.6% of the variation in student discipline explained by student management. The planning component in student management shows the best performance (mean = 3.89), followed by implementation (mean = 3.72) and evaluation (mean = 3.64). The aspect of student attendance has the highest score in discipline (mean = 4.12), while participation in school activities shows the lowest score (mean = 3.55). This study identifies several areas requiring improvement, including the gap between program planning and implementation, as well as the need for specific strategies to increase student participation in school activities. Recommendations include strengthening program implementation, enhancing the evaluation system, optimizing student participation, and developing peer mentoring programs.